2019
DOI: 10.3390/molecules24091713
|View full text |Cite
|
Sign up to set email alerts
|

Aspalathin-Rich Green Rooibos Extract Lowers LDL-Cholesterol and Oxidative Status in High-Fat Diet-Induced Diabetic Vervet Monkeys

Abstract: Type 2 diabetic patients possess a two to four-fold-increased risk for cardiovascular diseases (CVD). Hyperglycemia, oxidative stress associated with endothelial dysfunction and dyslipidemia are regarded as pro-atherogenic mechanisms of CVD. In this study, high-fat diet-induced diabetic and non-diabetic vervet monkeys were treated with 90 mg/kg of aspalathin-rich green rooibos extract (Afriplex GRT) for 28 days, followed by a 1-month wash-out period. Supplementation showed improvements in both the intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Thus, broadly indicating that by effectively regulating adipokine levels, CoQ 10 can greatly impact metabolic health in connection to ameliorating inflammation and oxidative stress in patients with T2D, NAFLD, or hypertension, as increasingly discussed [28][29][30]53]. Therapeutic benefits of CoQ 10 supplementation are essential important since its deficiency in the body or enhanced oxidation status has been linked with compromised metabolic function [24,54,55]. In fact, Gholami and colleagues [36] demonstrated that at the end of the intervention, CoQ 10 supplementation significantly improved its serum levels, including that of adiponectin while reducing that of MDA in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, broadly indicating that by effectively regulating adipokine levels, CoQ 10 can greatly impact metabolic health in connection to ameliorating inflammation and oxidative stress in patients with T2D, NAFLD, or hypertension, as increasingly discussed [28][29][30]53]. Therapeutic benefits of CoQ 10 supplementation are essential important since its deficiency in the body or enhanced oxidation status has been linked with compromised metabolic function [24,54,55]. In fact, Gholami and colleagues [36] demonstrated that at the end of the intervention, CoQ 10 supplementation significantly improved its serum levels, including that of adiponectin while reducing that of MDA in patients with T2D.…”
Section: Discussionmentioning
confidence: 99%
“…), according to a modified Downs and Black's guideline, as previously mentioned. The overall median score range of the included studies was 22 (19)(20)(21)(22)(23)(24), with five of them rated excellent (21-24 scores) and one rated as good (19 scores). In addition, KM used the Cohen's Kappa interrater to assess the degree of agreement in terms of quality assessment scores of the included studies [33].…”
Section: Risk Of Bias and Quality Of Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, several studies have alluded to the glucose and lipid modulating effects of Aspalathus linearis (rooibos) [26][27][28][29], a plant better known for its use as an herbal tea. The Aspalathus genus uniquely contains a C-glucosyl dihydrochalcone, aspalathin [29], which was demonstrated to stimulate glucose uptake in muscle tissues and increases insulin release in pancreatic beta cells, thus benefiting glucose homeostasis in various models of T2D [30]. In addition, rooibos has also been shown to have LDL-C lowering [31,32], and cardioprotective effects [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…A functional ingredient that gained interest in recent years due to its potential to modulate the metabolic syndrome is aspalathin-rich green rooibos extract (GRE) [ 6 ], shown to improve hyperglycaemia and HDL/LDL blood cholesterol profiles in non-human primates [ 7 ]. Aspalathin delivery in a RTD green rooibos iced tea presents a challenge as its stability is poor in solution, as shown by De Beer et al [ 8 ].…”
Section: Introductionmentioning
confidence: 99%